Cashing In or Paying Out? Analysis of the Relation Between Corporate Earnings and Cash - Ivanov, Stoyu I.; Vogel, Julian U. N. (Journal of Accounting and Finance, 2023)
This paper examines the relation between corporate earnings and cash in the US on annual basis in the period 2002 to 2022. We document that both earnings and cash holdings are non-stationary and therefore we use the Granger representation theorem and the methods of cointegration analysis and make an attempt to model the relation between these company variables. We document a negative sign of the cointegration coefficient estimate that is statistically significant. The statistical significance confirms that cash and earnings are cointegrated, and depend on each other. However, the significance of the models with earnings as the dependent variable is larger, and the coefficient estimates are more reliably negative. These results indicate that earnings depend on cash to a larger degree than cash depends on earnings.